Aptamer-Targeted Drug Delivery for Staphylococcus aureus Biofilm - Ommen, Pernille; Hansen, Line; Hansen, Bente K.; Vu-Quang, Hieu; Kjems, Jørgen; Meyer, Rikke L. (Frontiers in Cellular and Infection Microbiology, 2022)
Treatment of Staphylococcus aureus biofilm infections using conventional antibiotic therapy is challenging as only doses that are sublethal to the biofilm can be administered safely to patients. A potential solution to this challenge is targeted drug delivery. In this study, we tailored an aptamer-targeted liposomal drug delivery system for accumulation and delivery of antibiotics locally in S. aureus biofilm. In our search for a suitable targeting ligand, we identified six DNA aptamers that bound to S. aureus cells in biofilms, and we demonstrated that one of these aptamers could facilitate accumulation of liposomes around S. aureus cells inside the biofilm. Aptamer-targeted liposomes encapsulating a combination of vancomycin and rifampicin were able to eradicate S. aureus biofilm upon 24 h of treatment in vitro. Our results point to that aptamer-targeted drug delivery of antibiotics is a potential new strategy for treatment of S. aureus biofilm infections.